Person-Centered Expressive Arts Therapy in Clinical Settings: A Systematic Review of Quantitative Interventions - Bo, Zhang; Wang, Jia Hua; Abdullah, Azizah binti (Technium Social Sciences Journal, 2024)
Background: Person-Centered Expressive Arts Therapy (PCEAT) integrates the core concepts of humanistic psychology with the expressive arts to improve mental health and well-being. Its efficacy is substantiated by research across varied demographics for multiple psychological conditions. This review critically evaluates the effectiveness of PCEAT in clinical settings, employing quantitative research methods. Methods: The review followed PRISMA guidelines, and was registered at PROSPERO (CRD42023457126) searching eight databases for studies up to November 2023. Inclusion criteria were quantitative evaluations of PCEAT's effectiveness in clinical settings. Studies were assessed for risk of bias and categorized into three levels of evidence. Results: Three studies were included, focusing on dementia patients. These studies utilized various arts activities and showed improved emotional functioning and quality of life. However, all studies had high risk of bias, and the review did not perform a meta-analysis due to the heterogeneity of studies. Conclusions: Although PCEAT demonstrates potential benefits for dementia patients, the existing evidence remains limited and lacks robustness. Future research should incorporate more comprehensive and diverse studies to thoroughly assess PCEAT's efficacy in various populations and settings.